Detection of coronavirus in environmental surveillance and risk monitoring for pandemic control. (12th March 2021) - Yao, Linlin; Zhu, Wenting; Shi, Jianbo; Xu, Tailin; Qu, Guangbo; Zhou, Wenhua; Yu, Xue-Feng; Zhang, Xueji; Jiang, Guibin
Abstract : A schematic illustration of the environmental transmission of novel coronavirus (SARS-CoV-2 as an example) under different scenarios during the COVID-19 pandemic. Abstract : The novel human infectious coronaviruses (CoVs) responsible for severe respiratory syndromes have raised concerns owing to the global public health emergencies they have caused repeatedly over the past two decades. However, the ongoing coronavirus disease 2019 (COVID-19) pandemic induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has received unprecedented attention internationally. Monitoring pathogenic CoVs in environmental compartments has been proposed as a promising strategy in preventing the environmental spread and tracing of infectious diseases, but a lack of reliable and efficient detection techniques is still a significant challenge. Moreover, the lack of information regarding the monitoring methodology may pose a barrier to primary researchers. Here, we provide a systematic introduction focused on the detection of CoVs in various environmental matrices, comprehensively involving methods and techniques of sampling, pretreatment, and analysis. Furthermore, the review addresses the challenges and potential improvements in virus detection techniques for environmental surveillance.